The role of work location in associations between need satisfaction and well-being at work: a daily diary design among Dutch office workers - Roy Peijen; Irene M. W. Niks; Marianne H. J. van Zwieten; Karen M. Oude Hengel; Noortje Wiezer (BMC Public Health)
Abstract Background After a quick rise of remote work during the COVID-19 pandemic, hybrid working (i.e., combining remote and on-site work locations) is becoming common post-pandemic. This study aimed to investigate to what extent daily work location (i.e., office, home, or hybrid - a combination within the same day) affects daily associations between psychological need satisfaction (i.e., relatedness satisfaction and autonomy satisfaction) and well-being of office workers (i.e., perceived stress and work pleasure). Methods A daily diary study design with ecological momentary assessments (EMA) was used to investigate day-level relations between work location, need satisfaction, and employee well-being outcomes among 201 Dutch office workers. Measurements took place at the end of each working day (Mondays through Fridays) every month’s first week for three consecutive months. In total, we collected 1,448 daily observations of 201 employees. Multilevel regression models were performed to examine the relationship between daily need satisfaction of relatedness and autonomy, and their association with both daily work pleasure and daily work stress. Additionally, we explored whether work location serves as a moderator in these relationships. Results Employees reported higher relatedness satisfaction but less autonomy satisfaction on office or hybrid working days compared to home working days. Higher daily levels of relatedness and autonomy satisfaction were associated with increased work pleasure and reduced work stress. On office days, the positive relationship between relatedness satisfaction and work pleasure and the negative relationship between relatedness satisfaction and work stress were more pronounced than on home working days. In contrast, the positive relationship between autonomy satisfaction and work pleasure as well as its negative relationship with stress were consistent across work locations, showing no variation between office, home or combined settings. Conclusions This study shows that daily work location may be an important factor to consider in the context of (enhancing) daily need satisfaction and daily employee well-being. Different work locations can contribute to daily need satisfaction and employee well-being in different ways. It seems particularly important that working in the office is organized in a way that employees are able to make meaningful connections with others.